Perempuan dalam Ujian Akhlak Nabi Yusuf a.s. dan Nabi Sulaiman a.s.: Studi Tematik Tafsir al-Marāghī - Siti Emma Siregar; Safria Andy (CV Global Research Publication, 2026)
This research aims to examine the form of moral tests of Prophet Yusuf p.b.u.h and Prophet Sulaiman p.b.u.h in the Qur'an based on Tafsir al-Marāghī. This research uses a library research method with a thematic interpretation approach through analysis of verses related to the two stories. The research results show that Prophet Yusuf p.b.u.h faced moral tests in the form of temptation, pressure and slander which required steadfastness of faith, self-control and the maintenance of honor. Meanwhile, Prophet Sulaiman p.b.u.h faced a leadership test through giving gifts from Queen Balqis which tested his integrity, wisdom, and attitude towards power and wealth. Research findings show that Tafsir al-Marāghī depicts different test patterns in the two stories, but has the same main values, namely strong faith, commitment to truth, and the ability to control oneself from the influence of lust and worldly interests. Thus, the moral test in the Qur'an is not only individual, but also includes social and leadership dimensions in the formation of the character of a believer.